2023
DOI: 10.3390/microorganisms11123002
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacterial Diversity Responds to Long-Term Establishment of Perennial Legumes in Warm-Season Grassland at Two Soil Depths

Adesuwa Sylvia Erhunmwunse,
Victor Alonso Guerra,
Jung-Chen Liu
et al.

Abstract: The introduction of rhizoma peanut (RP Arachis glabrata Benth) into bahiagrass (Paspalum notatum Flüggé) may require time to develop stable plant–soil microbe interactions as the microbial legacy of the previous plant community may be long-lasting. A previous study showed that <2 years of introducing rhizoma peanut into bahiagrass pastures minimally affected soil bacterial diversity and community composition. In this study, we compared the effects of the long-term inclusion of rhizoma peanut (>8 years) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…The findings of this study demonstrated that in the Hunan tobacco–rice multiple cropping fields, the ability of soil bacterial communities to metabolize carbon decreased with increasing soil depth and that both the range of species and abundance of the soil bacterial community generally decreased with increasing soil depth. Similar to the findings of Erhunmwunse et al 38 , the bacterial diversity peaked at 10 cm from the top of the soil profile. Through LEfSe analysis, we found that the bacterial communities with large differences in soil composition in each layer were correlated with the intensity of carbon source metabolism.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of this study demonstrated that in the Hunan tobacco–rice multiple cropping fields, the ability of soil bacterial communities to metabolize carbon decreased with increasing soil depth and that both the range of species and abundance of the soil bacterial community generally decreased with increasing soil depth. Similar to the findings of Erhunmwunse et al 38 , the bacterial diversity peaked at 10 cm from the top of the soil profile. Through LEfSe analysis, we found that the bacterial communities with large differences in soil composition in each layer were correlated with the intensity of carbon source metabolism.…”
Section: Discussionsupporting
confidence: 88%